SAY NO to mild ovarian stimulation for all poor responders: it is time to realize that not all poor responders are the same. Issue 9 (24th August 2020) - Polyzos, N P; Popovic-Todorovic, B
ABSTRACT: Over the last 25 years, a vast body of literature has been published evaluating different treatment modalities for the management of poor ovarian responders. Despite the evidence that maximizing ovarian response can improve the chances of live born babies in poor responders, there are still voices suggesting that all poor responders are the same, irrespective of their age and their actual ovarian reserve. This has resulted in the suggestion of adopting a mild ovarian stimulation approach for all poor responders, based on the results of several trials which failed to identity differences when comparing mild and more intense stimulation in predicted poor responders. The current article analyzes in detail these studies and discusses the shortcomings in terms of type of population included, outcomes and settings performed, which may actually be responsible for the belief that only mild stimulation should be used. In the era of individualization in medicine, it must be realized that there are subgroups of predicted poor responders who will benefit from an individual rather than 'one fits all' mild stimulation approach and thus we should provide the same standard of treatment for all our poor responder patients.